Do poor people’s dreams ever come true? Educational Aspirations and Lived Realities in Urban Slums in Dhaka, Bangladesh - Sultan, Maheen; Saeger, Jennifer; Rashid, Sabina F.; Haque, Mohammed Ashraful; Khondaker, Sahida (Springer Link, 2022)
This article was published in The The European Journal of Development Research [©2022 Published by Springer Journal] and the definite version is available at: https://doi.org/10.1057/s41287-021-00476-z The Article's website is at: https://link.springer.com/article/10.1057/s41287-021-00476-z#citeas